IMPORTANCE OF CULTURAL HERITAGE OBJECTS OF KASHKADARYA REGION IN THE PERSPECTIVE OF DEVELOPMENT OF PILGRIMAGE TOURISM (American Journal of Interdisciplinary Research and Development, 2024)
This article describes the personalities of scholars who grew up in the Karshi district of Kashkadarya region, their contributions to the development of Islam, the spiritual and educational significance of their life paths and works that are examples of creativity, and the transformation of the places where they lived into holy places and places of pilgrimage. Also, in the article, the state of architectural monuments related to shrines of Kashkadarya region, Karshi district, their number, history, today's role of these shrines in the development of pilgrimage tourism and the importance of this cultural heritage in increasing the visit of our people and foreign tourists are covered.